How Important Gender Inequality in Education on Poverty Reduction? Indonesian Case - Hanim, Wasifah; Apriliana, Tria (International Journal of Psychosocial Rehabilitation, 2020)
Gender inequality is considered an important issue in development that can affect poverty alleviation. The gap reduction between men and women in education would affect a number of development goals. This study attempts to reveal the impact of gender inequality in education on poverty in Indonesia. This research used the Ordinary Least Squares (OLS) model to get the degree of gender inequality in education. With data from Badan Pusat Statistik (BPS) between 2010–2018, we used several parameters like the number of poor people, the number of gender inequality in education, inflation rate, unemployment rate, and opennes. The results show that increasing education levels for women would have a strong impact on poverty reduction in Indonesia.